Linking ecosystem accounting to environmental planning and management: Opportunities and barriers using a case study from the Australian Capital Territory. Issue 142 (April 2023) - Chen, Yuqing; Vardon, Michael; Keith, Heather; Van Dijk, Albert; Doran, Bruce
Abstract: The System of Environmental Economic Accounting (SEEA) has the potential to support decision making but there are few cases of their application to public policy or planning. In this paper we review five government policies related to land use planning and environmental management in the Australian Capital Territory (ACT), assess the data available to inform these policies and link the polices to the accounts that could assist with their implementation, evaluation and update. We find that a range of SEEA-based accounts are potentially useful for the plans and strategies reviewed. Data available for accounts are of varying quality, scattered and are not integrated nor regularly summarised. The available data were to produce accounts for ecosystem extent and land cover, and these provide a platform for continuing engagement with the ACT government and for developing accounts for ecosystem services, ecosystem condition and environmental protection expenditure that could inform ACT policy for land use planning, management of ecosystems, protected areas, and urban forests. Six steps for developing ecosystem accounts to support policy are recommended to accounts producers and three priority actions for SEEA-based accounting to support environmental management in the ACT are identified. Preparing the accounts and linking them directly to existing plans and strategies is a first step to acceptance and use of SEEA in the ACT and elsewhere. Highlights: Ecosystem accounts can be mapped to policy and be useful to decision makers. Ecosystem accounts can inform the different parts of the policy cycle. Land and ecosystem extent accounts can be produced and are the starting point for ecosystem condition and service accounts. Data gaps and deficiencies on the physical environment can be overcome through use of global datasets and methods. The development of spatially referenced economic data must be encouraged.